CHARACTERIZATION AND SPATIAL DISTRIBUTION OF ETHNO-CULTURAL TOURISM RESOURCES IN KADUNA STATE, NIGERIA - Ibrahim, Aliyu Hassan; Adamu, Hassan Ibrahim (FUDMA JOURNAL OF SCIENCES, 2021)
The paper examined the spatial distribution and characteristics of ethno-cultural tourism resources available in different ethnic communities in Kaduna State, Nigeria. The sampled communities are Ham, Fulani, Hausa, Kagoro, Adara and Gbagyi, field observations were also carried out for holistic resource inventory in the ethnic communities. Documentary data were obtained from desk review method; information on tourism resources available in each ethnic community. The findings of the study reveal that the ethno-cultural resources were characterized into three groups that are made up of archaeological/historical monuments, cultural and festival activities, and artifacts; while the nature-based tourism, resources were also sub-divided into geomorphic and hydrological features. The study recommends that There is the need for private public partnership (PPP) to foster visible ethno-cultural tourism development projects (tourism potential development, provision of social amenities to enhance competitive advantage and enlightenment campaigns), since the local and state Governments (basically in terms of infrastructural developing and policy issue that will providing an enabling environment for tourism projects to strive) cannot do all or meet all the yearnings of the people.